UK Joint Advisory Group consensus statements for training and certification in endoscopic retrograde cholangiopancreatography - Siau, Keith; Keane, Margaret G; Steed, Helen; Caddy, Grant; Church, Nick; Martin, Harry; McCrudden, Raymond; Neville, Peter; Oppong, Kofi; Paranandi, Bharat; Rasheed, Ashraf; Sturgess, Richard; Hawkes, Neil D; Webster, George; Johnson, Gavin; on behalf of the Joint Advisory Group on Gastrointestinal Endoscopy (JAG) (Endoscopy International Open, 2022)
Background and study aims Despite the high-risk nature of endoscopic retrograde cholangiopancreatography (ERCP), a robust and standardized credentialing process to ensure competency before independent practice is lacking worldwide. On behalf of the Joint Advisory Group (JAG), we aimed to develop evidence-based recommendations to form the framework of ERCP training and certification in the UK. Methods Under the oversight of the JAG, a modified Delphi process was conducted with stakeholder representation from the British Society of Gastroenterology, Association of Upper Gastrointestinal Surgeons, trainees and trainers. Recommendations on ERCP training and certification were formulated after formal literature review and appraised using the GRADE tool. These were subjected to electronic voting to achieve consensus. Accepted statements were peer-reviewed by JAG and relevant Specialist Advisory Committees before incorporation into the ERCP certification pathway.Results In total, 27 recommendation statements were generated for the following domains: definition of competence (9 statements), acquisition of competence (8 statements), assessment of competence (6 statements) and post-certification support (4 statements). The consensus process led to the following criteria for ERCP certification: 1) performing ≥ 300 hands-on procedures; 2) attending a JAG-accredited ERCP skills course; 3) in modified Schutz 1–2 procedures: achieving native papilla cannulation rate ≥80%, complete bile duct clearance ≥ 70 %, successful stenting of distal biliary strictures ≥ 75 %, physically unassisted in ≥ 80 % of cases; 4) 30-day post-ERCP pancreatitis rates ≤5 %; and 5) satisfactory performance in formative and summative direct observation of procedural skills (DOPS) assessments.Conclusions JAG certification in ERCP has been developed following evidence-based consensus to quality assure training and to ultimately improve future standards of ERCP practice.